Religious Ability: assessment of early childhood aged 5-6 years - Asep Mulyana; Diani Magasida; Aip Saripudin (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2022)
Religious assessment in early childhood aims to determine the child's development and plan the stimulation that will be carried out by the teacher in the next lesson. This study aims to identify the religious abilities of children aged 5-6 years in the city of Cirebon. This research was conducted in two stages, namely conducting a preliminary study and conducting observations in 13 kindergartens in the city of Cirebon. Data were analyzed using qualitative descriptive supported by quantitative data. The results showed that 85% of children aged 5-6 years in the city of Cirebon have shown good religious abilities. This can be seen from the child's ability to know God, carry out worship according to his beliefs, respect his parents, and love God's creation. The findings show that teachers have stimulated children through daily habituation. Habituation is not only done at school but also done at home. The teacher collaborates well with parents through intensive communication both through whatsup groups and contact books. Keywords: Assessment, Early Childhood, Development of religious values